Pendampingan Keluarga Pasien dalam Mengelola Kecemasan Sebelum Prosedur Anestesi - Happy Nurhayati; Fransi Arsani (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2022)
Anxiety before anesthesia procedures is a common problem in patients and their families. High levels of anxiety can affect the patient's physiological stability and postoperative outcomes. The family assistance program aims to provide education and emotional support to reduce anxiety before anesthesia. The methods used include socialization, interactive education, and evaluation of the patient's family's understanding before and after the intervention. This study involved 15 respondents at RSIA Aisyiyah Klaten. The results showed that after the intervention, there was a decrease in the level of anxiety in the patient's family from 70% to 35%. This finding indicates that family education and assistance have an important role in improving the mental readiness of patients and their families before undergoing anesthesia.